Effects of alkali ions on the optical properties, bandwidth flatness, and gain coefficient of near-infrared emission spectra of Er3+-doped zinc silicate glass - Nguyễn, Đình Trung (ELSEVIER, 2024)
In this paper, we investigate and report the effects of alkali ions A+ (A+ = Li+, Na+, K+) on the optical properties, bandwidth flatness (BFN), gain coefficient (G(λ)) for the near-infrared (NIR) emission spectra of Er3+-doped SiO2–ZnO–La2O3 (SZL) zinc silicate glass. With the change in the composition of A+ ions in the order from not containing any A+ ions → Li+ → Na+ → K+ → containing all three A+ ions including Li+, Na+, and K+, the direct and indirect bandgap (DBG and IBG), the absorption cross-section (σabs(λ)), the emission cross-section (σems(λ)), and the G(λ) parameters of Er3+-doped SZL glasses were determined to increase gradually. NIR emission in tensities of Er3+-doped at 4 I13/2 → 4 I15/2 transition under excitations of both 808 and 980 nm LD all were significantly increased with the composition of A+ ions varies in order from not containing A+ ions → Li+ → Na+ → K+ → containing all three A+ ions. The reasons for the influence of A+ ions on the UC and NIR emission intensities of Er3+-doped in SZL glass are investigated and discussed. In addition, upconversion (UC) emission spectra of Er3+-doped, CIE 1931(x; y) coordinates and color region for UC emission spectra of Er3+-doped SZL glasses with different compositions of A+ ions under excitation of 980 nm laser diode (LD) are also determined